Venous Thromboembolism in Cancer: An Update of Treatment and Prevention in the Era of Newer Anticoagulants - Qureshi, Waqas; Ali, Zeeshan; Amjad, Waseem; Alirhayim, Zaid; Farooq, Hina; Qadir, Shayan; Khalid, Fatima; Al-Mallah, Mouaz H. (Frontiers in Cardiovascular Medicine, 2016)
Cancer patients are at major risk of developing venous thromboembolism (VTE), resulting in increased morbidity and economic burden. While a number of theories try to explain its pathophysiology, its risk stratification can be broadly done in cancer-related, treatment–related, and patient-related factors. Studies report the prophylactic use of thrombolytic agents to be safe and effective in decreasing VTE-related mortality/morbidity especially in postoperative cancer patients. Recent data also suggest the prophylactic use of low molecular weight Heparins (LMWHs) and Warfarin to be effective in reducing VTEs related to long-term central venous catheter use. In a double-blind, multicenter trial, a new ultra-LMWH Semuloparin has shown to be efficacious in preventing chemotherapy-associated VTE’s along with other drugs, such as Certoparin and Nadoparin. LMWHs are reported to be very useful in preventing recurrent VTEs in advanced cancers and should be preferred over full dose Warfarin. However, their long-term safety beyond 6 months has not been established yet. Furthermore, this paper discusses the safety and efficacy of different drugs used in the treatment and prevention of recurrent VTEs, including Bemiparin, Semuloparin, oral direct thrombin inhibitors, parenteral and direct oral factor Xa inhibitors.